Evaluation of mass and stiffness properties of structure through system identification - Kamatchi, P.; Priya, C. Bharathi; Prakash, Neethu; Kumar, K. Sathish (Journal of Structural Engineering, 2024)
Seismic safety evaluation of existing building is a challenging task due to the non-accessibility of structural details. Studies are reported in literature on application of system identification techniques for extraction of modal properties of existing structures for damage detection and health monitoring objectives. Present study aims at identifying a simplified methodology to determine the mass and stiffness properties of a system for which the input and output acceleration responses are available. The methodology has been demonstrated for a three storey steel frame with RC slab for eight earthquake time histories using shake table test results. The modal parameters such as frequencies, mode shapes and damping ratios of the building are estimated using frequency response functions. Vital structural parameters governing the dynamic response of the building viz., mass, stiffness and damping are obtained using the frequency characteristics extracted. The proposed methodology can be used for obtaining the frequencies, mode shapes, mass and stiffness matrices of the structure, where access to structural details are limited.